Beneficial Use of Dredged Materials in Great Lakes Commercial Ports for Transportation Projects - Yu, Hua (My University, 2015)
1.1 . Scope This chapter briefly introduces the problems and opportunities associated with dredged material DM) management in the Great Lakes region and historical options for beneficial use of DM. The overall objective of the project and the structure and scope of this report are summarized.
Keywords: Beneficial Use; Dredged Materials